ANALISIS DAN PERANCANGAN SISTEM E-ABSENSI MENGGUNAKAN QR-CODE BERBASIS WEB DIKANTOR PEMERINTAHAN DESA BINAMANG - safira, safiradewitaananda; Deddy Gusman; Safni Marwa (Universitas Pahlawan Tuanku Tambusai, 2024)
Attendance systems are crucial in monitoring employee presence within governmental organizations, and attendance is one of the key aspects of performance evaluation in the government sector. The attendance system has evolved over time to find the most efficient and convenient method for the Binamang Village Office. Currently, the attendance system at the Binamang Village Office, located in XIII Koto Kampar District, still uses a manual method, where employees sign their names on attendance sheets provided at the village office. Given the advancements and use of technology, particularly information technology, the presence of gadgets such as smartphones and communication networks (internet) enables the use of digital/electronic attendance (e-attendance) to facilitate activities and work scope for employees, making supervision more practical and efficient. The purpose of this study is to design technological tools that support a digital/electronic attendance system (e-attendance) using Quick Response Code (QR Code). With the development of the attendance system at the Binamang Village Office, a system analysis is required. This research employs the waterfall development method, and the analysis is conducted using the PIECES method (Performance, Information, Economic, Control, Efficiency, Service). The results of the analysis using the PIECES method will be elaborated into a system design for processes, databases, and interfaces.